Pelatihan Pengembangan Aplikasi Mobile Menggunakan Flutter untuk Pemula pada Guru dan Dosen Perkumpulan Profesi Multimedia dan Teknologi Informasi (PPMULTINDO) (Bumi: Jurnal Hasil Kegiatan Sosialisasi Pengabdian kepada Masyarakat, 2026)
The development of information technology, particularly the use of smartphones, has changed human activity patterns and significantly impacted the education sector. The "one-stop-shop" concept reflects the use of mobile devices as centers for various activities, including learning. This situation drives the need for innovation in the development of adaptive and interactive learning media. One solution that can be developed is an Android-based mobile application using Flutter, which can increase the effectiveness and efficiency of the learning process. The Association of Multimedia and Information Technology Professionals (PPMultindo), an organization focused on technology, has developed an Android-based learning platform. This platform is designed to provide flexible access to materials, support interactivity, and facilitate collaboration between educators. Features such as learning analysis, material recommendations, and automatic evaluation are expected to improve the quality of the learning experience. However, the implementation of this technology still faces various challenges, including limited technological competence of educators, inadequate infrastructure, and adjustments to curriculum needs. Therefore, collaborative efforts are needed to optimize the use of mobile technology to support educational transformation in the digital era.